METHODS OF ANTI-CRISIS RESTRUCTURING FOR TOWN-FORMING ORGANIZATIONS - K. A. Rubanova (Стратегические решения и риск-менеджмент)
A distinguishing feature of town-forming organization is a high socio-economic importance, and therefore very large number of persons, including the government, is interested in its functioning. The economic problems of financial recovery and enterprise restructuring can only be solved at the state level. However, the blind "infusion" of money to any town-forming organizations in a state of crisis is not a solution. The purpose of this work is to considerate the cases of state intervention during the anti-crisis restructuring of town-forming organization and assessment the suitability of such involvement.